A multicellular brain spheroid model for studying the mechanisms and bioeffects of ultrasound-enhanced drug penetration beyond the blood‒brain barrier - Anurag N. Paranjape; Leonardo D’Aiuto; Wenxiao Zheng; Xucai Chen; Flordeliza S. Villanueva (Scientific Reports, 2024)
Abstract The blood‒brain barrier (BBB) acts as a hindrance to drug therapy reaching the brain. With an increasing incidence of neurovascular diseases and brain cancer metastases, there is a need for an ideal in vitro model to develop novel methodologies for enhancing drug delivery to the brain. Here, we established a multicellular human brain spheroid model that mimics the BBB both architecturally and functionally. Within the spheroids, endothelial cells and pericytes localized to the periphery, while neurons, astrocytes, and microglia were distributed throughout. Ultrasound-targeted microbubble cavitation (UTMC) is a novel noninvasive technology for enhancing endothelial drug permeability. We utilized our three-dimensional (3D) model to study the feasibility and mechanisms regulating UTMC-induced hyperpermeability. UTMC caused a significant increase in the penetration of 10 kDa Texas red dextran (TRD) into the spheroids, 100 µm beyond the BBB, without compromising cell viability. This hyperpermeability was dependent on UTMC-induced calcium (Ca2+) influx and endothelial nitric oxide synthase (eNOS) activation. Our 3D brain spheroid model, with its intact and functional BBB, offers a valuable platform for studying the bioeffects of UTMC, including effects occurring spatially distant from the endothelial barrier.